Avaliação ecológica do efeito combinado de contaminantes ambientais - Vidal, Tânia Daniela da Silva (2014)
The assessment of ecological status of lotic freshwater bodies, based on stringent criteria of classification, has been defined by the Water Framework Directive (WFD), as a result of the implementation and optimization of methodologies that integrate physico-chemical, biological, and hydromorphological parameters. It is recognized that the application of this methodology is not easy, because it requires deep technical and scientific knowledge; it is time consuming in its application involving high financial costs. Thus, the main objective of this study was the development of cheaper and faster complementary methodologies that may contribute to the technical application of the classification criteria defined by the WFD, achieving the same final results of evaluation. In order to achieve this main goal, the river Mau, a small mountain river subjected to different stressors (eg, metals, pesticides), was established as the main sampling area. This thesis reviewed the historical development of various biotic indexes and its application in assessing water quality, especially highlighting the new paradigm defined by the WFD, and the corresponding actions developed for optimization and intercalibration of methodologies, evaluating the final state of water bodies. The ecological spatiotemporal characterization of the river Mau focused on the application of the WFD methodology, using at this stage only macroinvertebrates collected during four seasons. Results were compared with historical data of the last three years and they demonstrated that the river is in good condition. However, the ecological quality decreased at certain locations indicating that organisms were subjected to some type of disturbance. As the ecological quality can be conditioned by pulses of contamination from the sediments, in environmental adverse conditions, assays were performed with elutriates, obtained from sediments collected near the mining complex Braçal-Palhal. Results showed that this method was effective achieving the state of contamination, which may be important in prioritizing/scoring of critical areas within river ecosystems potentially impacted, using the WFD methodology. However, this methodology requires the collection of sediment which can promote the modification and / or loss of contaminants. To solve this potential problem, we developed a new methodology to obtain similar results. For this, we used a benthic microalga, belonging to the Portuguese flora, sensitive to organic pollution and metals. This methodology was optimized for application in situ, by immobilization of diatom in calcium alginate beads. The results showedthat their sensitivity and normal growth rate are similar to data obtained when used free cells of diatom. This new methodology allowed the achievement of a very quick response on the degree of contamination of a site, providing a complementary methodology to WFD.